Az afrikai tamtam-ok avagy résdobok története és típusai - Brauer-Benke, József (Afrika Tanulmányok / Hungarian Journal of African Studies, 2018)
A general survey of data leads one to conclude that, even though the slit drum type of instruments, owing to their simple structure, could have developed in any place with abundant tree cover, the available data suggest that the introduction of this instrument type, or the underlying idea, into the equatorial belt can be linked to the migration of speakers of Austronesian languages. After its introduction, however, the instrument type developed in highly localized fnctions and forms. On this basis the widespread slit drum types of Equatorial Africa were passed on in an East-to-West direction; the absence of these instruments in Southern Africa and the date of arrival of Austronesian-speaking groups in Africa suggest the possibility that the appearance of slit drums in Africa can be dated to the period between the 6th and 10th centuries. The communicative function and prestige value of this instrument type led to its wide adoption among the ethnic groups of the Congo basin in particular. Contrastingly, a major hindrance to its wider distribution over West Africa may have been the presence of a rival candidate for its communicative function (the membranophonic „talking drums”), as well as changes in the animistic religious concepts linked to this instrument type, a result of widepread conversion to Islam from the 14th century. In Eastern Africa too conversion to Islam from the 11th century and the associated spead of the use of Swahili may have been a significant factor, given the fact that Swahili, while a Bantu language, is not a tone language, and thus the diminished communicative potential of these instruments, dependent on tone, as well as the shrinking ritual aspects of their use as symbols of chiefly authority must have led to the gradual decline of the use of slit drums in this region.